Comparative Virulence and Genomic Analysis of Streptococcus suis Isolates - Nicholson, Tracy L.; Waack, Ursula; Anderson, Tavis K.; Bayles, Darrell O.; Zaia, Sam R.; Goertz, Isaiah; Eppinger, Mark; Hau, Samantha J.; Brockmeier, Susan L.; Shore, Sarah M. (Frontiers in Microbiology, 2021)
Streptococcus suis is a zoonotic bacterial swine pathogen causing substantial economic and health burdens to the pork industry. Mechanisms used by S. suis to colonize and cause disease remain unknown and vaccines and/or intervention strategies currently do not exist. Studies addressing virulence mechanisms used by S. suis have been complicated because different isolates can cause a spectrum of disease outcomes ranging from lethal systemic disease to asymptomatic carriage. The objectives of this study were to evaluate the virulence capacity of nine US S. suis isolates following intranasal challenge in swine and then perform comparative genomic analyses to identify genomic attributes associated with swine-virulent phenotypes. No correlation was found between the capacity to cause disease in swine and the functional characteristics of genome size, serotype, sequence type (ST), or in vitro virulence-associated phenotypes. Numerous differences among the predicted protein coding sequences between highly virulent and nonvirulent isolates were identified. While these none of these predicted protein coding sequences have been previously characterized as potential virulence factors, this analysis does provide a reliable one-to-one assignment of specific genes of interest that could prove useful in future allelic replacement and/or functional genomic studies. Collectively, this report provides a framework for future allelic replacement and/or functional genomic studies investigating genetic elements underlying the spectrum of disease outcomes caused by S. suis isolates.